Serological evidence of Leptospira sp. in humans from Fernando de Noronha Island, Brazil. (August 2020) - Carvalho, Maria da Conceição; Ribeiro-Andrade, Müller; de Oliveira, Pollyanne Raysa Fernandes; de Melo, Renata Pimentel Bandeira; Aragão, Breno Bezerra; Viana, Maira Pôrto; de Azevedo, Sergio Santos; Rodrigues Magalhães, Fernando Jorge; Mota, Rinaldo Aparecido
Highlights: This is the first report on Leptospira spp. in humans from island, Brazil. The island is home to Leptospiras which may pose some risk of infection to the population. Provide health education to the population on the risks and impact of leptospirosis. This island needs active surveillance to identify suspected cases. Abstract: The prevalence of leptospirosis in humans is highly variable, being influenced by climatic factors, the presence of reservoirs, occupational exposure, recreational activity, and socioeconomic conditions. The objective of this study was to estimate the prevalence of Leptospira sp. and identify the predominant human serovars on the island of Fernando de Noronha, Brazil, based on a microscopic agglutination test. The prevalence of anti- Leptospira antibodies was 1.17% (4/341; I.C. 0.46%–2.98%), with the predominance of serovars Icterohaemorrhagiae, Javanica, Mini and Louisiana. This is the first study on the occurrence of antibodies against Leptospira sp. in humans in Fernando de Noronha and highlights the need to implement control and prevention strategies in this island environment.